CO2 Capture for Dry Reforming of Natural Gas: Performance and Process Modeling of Calcium Carbonate Looping Using Acid Based CaCO3 Sorbent - Zubir M.A.; Afandi N.; Manap A.; Hamid A.A.; Ayodele B.V.; Liu W.; Abd Hamid M.K. (Frontiers Media S.A., 2023)
Alumina; Aluminum oxide; Calcite; Calcium carbonate; Carbon dioxide process; Chemical reactors; Coal; Computer software; Fluidized beds; Fossil fuel power plants; Gas emissions; Greenhouse gases; Industrial emissions; Lime; Limestone; Methane; Natural gas; Natural gasoline plants; Oxalic acid; Process engineering; Sorbents; Sorption; Aspen Plus Simulators; Attrition resistances; Coal-fired power plant; Dry reforming-of-methane; Fluidized bed reactors; Industrial activities; Principal Components; Supporting material; Carbon dioxide